Transport Layer Obscurity: Circumventing SNI Censorship on the TLS-Layer - Niere, Niklas; Lange, Felix; Merget, Robert; Somorovsky, Juraj (2025 IEEE Symposium on Security and Privacy (SP))
HTTPS composes large parts of today’s Internet traffic and has long been subject to censorship efforts in different countries. While censors analyze the Transport Layer Security (TLS) protocol to block encrypted HTTP traffic, censorship circumvention efforts have primarily focused on other protocols such as TCP. In this paper, we hypothesize that the TLS protocol offers previously unseen opportunities for censorship circumvention techniques. We tested our hypothesis by proposing possible censorship circumvention techniques that act on the TLS protocol. To validate the effectiveness of these techniques, we evaluate their acceptance by popular TLS servers and successfully demonstrate that these techniques can circumvent censors in China and Iran. In our evaluations, we discovered 38—partially standard-compliant—distinct censorship circumvention techniques, which we could group into 11 unique categories. Additionally, we provide novel insights into how China censors TLS traffic by presenting evidence of at least three distinct censorship appliances. We suspect that other parts of China’s censorship apparatus and other censors exhibit similar structures and advocate future censorship research to anticipate them. With this work, we hope to aid people affected by censorship and stimulate further research into censorship circumvention using cryptographic protocols.

STEK Sharing is Not Caring: Bypassing TLS Authentication in Web Servers using Session Tickets - Hebrok, Sven Niclas; Storm, Tim Leonhard; Cramer, Felix Matthias; Radoy, Maximilian Manfred; Somorovsky, Juraj (34th USENIX Security Symposium)

STEK Sharing is Not Caring: Bypassing TLS Authentication in Web Servers using Session Tickets - Hebrok, Sven; Storm, Tim Leonhard; Cramer, Felix Matthias; Radoy, Maximilian; Somorovsky, Juraj (34th USENIX Security Symposium (USENIX Security 25))

Security Implications of Malicious G-Codes in 3D Printing - Rossel, Jost; Mladenov, Vladislav; Wördenweber, Nico; Somorovsky, Juraj (Proceedings of the 34th USENIX Security Symposium)
The rapid growth of 3D printing technology has transformed a wide range of industries, enabling the on-demand production of complex objects, from aerospace components to medical devices. However, this technology also introduces significant security challenges. Previous research highlighted the security implications of G-Codes—commands used to control the printing process. These studies assumed powerful attackers and focused on manipulations of the printed models, leaving gaps in understanding the full attack potential. In this study, we systematically analyze security threats associated with 3D printing, focusing specifically on vulnerabilities caused by G-Code commands. We introduce attacks and attacker models that assume a less powerful adversary than traditionally considered, broadening the scope of potential security threats. Our findings show that even minimal access to the 3D printer can result in significant security breaches, such as unauthorized access to subsequent print jobs or persistent misconfiguration of the printer. We identify 278 potentially malicious G-Codes across the attack categories Information Disclosure, Denial of Service, and Model Manipulation. Our evaluation demonstrates the applicability of these attacks across various 3D printers and their firmware. Our findings underscore the need for a better standardization process of G-Codes and corresponding security best practices.

On the Security of SSH Client Signatures - Bäumer, Fabian; Brinkmann, Marcus; Radoy, Maximilian; Schwenk, Jörg; Somorovsky, Juraj (Proceedings of the 2025 ACM SIGSAC Conference on Computer and Communications Security)

I(ra)nconsistencies: Novel Insights into Iran’s Censorship - Lange, Felix; Niere, Niklas; von Niessen, Jonathan; Suermann, Dennis; Heitmann, Nico; Somorovsky, Juraj (Proceedings on Privacy Enhancing Technologies)
Iran employs one of the most prominent Internet censors in the world. An important part of Iran’s censorship apparatus is its analysis of unencrypted protocols such as HTTP and DNS. During routine evaluations of Iran’s HTTP and DNS censorship, we noticed several properties we believe to be unknown today. For instance, we found injections of correct static IPs for some domains such as google.com on the DNS level, unclear HTTP version parsing, and correlations between DNS and HTTP censorship. In this paper, we present our findings to the community and discuss possible takeaways for affected people and the censorship circumvention community. As some of our findings left us bewildered, we hope to ignite a discussion about Iran’s censorship behavior. We aim to use the discussion of our work to execute a thorough analysis and explanation of Iran’s censorship behavior in the future.

Security Analysis of BigBlueButton and eduMEET - Heitmann, Nico; Siewert, Hendrik; Moog, Sven; Somorovsky, Juraj (Applied Cryptography and Network Security)
Video conferencing systems have become an indispensable part of our world. Using video conferencing systems implies the expectation that online meetings run as smoothly as in-person meetings. Thus, online meetings need to be just as secure and private as in-person meetings, which are secured against disruptive factors and unauthorized persons by physical access control mechanisms. To show the security dangers of conferencing systems and raise general awareness when using these technologies, we analyze the security of two widely used research and education open-source video conferencing systems: BigBlueButton and eduMEET. Because both systems are very different, we analyzed their architectures, considering the respective components with their main tasks, features, and user roles. In the following systematic security analyses, we found 50 vulnerabilities. These include broken access control, NoSQL injection, and denial of service (DoS). The vulnerabilities have root causes of different natures. While BigBlueButton has a lot of complexity due to many components, eduMEET, which is relatively young, focuses more on features than security. The sheer amount of results and the lack of prior work indicate a research gap that needs to be closed since video conferencing systems continue to play a significant role in research, education, and everyday life.

In Search of Partitioning Oracle Attacks Against TLS Session Tickets - Radoy, Maximilian Manfred; Hebrok, Sven Niclas; Somorovsky, Juraj (Lecture Notes in Computer Science)

TLS-Attacker: A Dynamic Framework for Analyzing TLS Implementations - Bäumer, Fabian; Brinkmann, Marcus; Erinola, Nurullah; Hebrok, Sven Niclas; Heitmann, Nico; Lange, Felix; Maehren, Marcel; Merget, Robert; Niere, Niklas; Radoy, Maximilian Manfred; Schmidt, Conrad; Schwenk, Jörg; et al. (Proceedings of Cybersecurity Artifacts Competition and Impact Award (ACSAC ’24))
TLS-Attacker is an open-source framework for analyzing Transport Layer Security (TLS) implementations. The framework allows users to specify custom protocol flows and provides modification hooks to manipulate message contents. Since its initial publication in 2016 by Juraj Somorovsky, TLS-Attacker has been used in numerous studies published at well-established conferences and helped to identify vulnerabilities in well-known open-source TLS libraries. To enable automated analyses, TLS-Attacker has grown into a suite of projects, each designed as a building block that can be applied to facilitate various analysis methodologies. The framework still undergoes continuous improvements with feature extensions, such as DTLS 1.3 or the addition of new dialects such as QUIC, to continue its effectiveness and relevancy as a security analysis framework.
Keywords: SSL; TLS; DTLS; Protocol State Fuzzing; Planning Based

Turning Attacks into Advantages: Evading HTTP Censorship with HTTP Request Smuggling - Müller, Philipp; Niere, Niklas; Lange, Felix; Somorovsky, Juraj (Proceedings on Privacy Enhancing Technologies)
Many countries limit their residents' access to various websites. As a substantial number of these websites do not support TLS encryption, censorship of unencrypted HTTP requests remains prevalent. Accordingly, circumvention techniques can and have been found for the HTTP protocol. In this paper, we infer novel circumvention techniques on the HTTP layer from a web security vulnerability by utilizing HTTP request smuggling (HRS). To demonstrate the viability of our techniques, we collected various test vectors from previous work about HRS and evaluated them on popular web servers and censors in China, Russia, and Iran. Our findings show that HRS can be successfully employed as a censorship circumvention technique against multiple censors and web servers. We also discover a standard-compliant circumvention technique in Russia, unusually inconsistent censorship in China, and an implementation bug in Iran. The results of this work imply that censorship circumvention techniques can successfully be constructed from existing vulnerabilities. We conjecture that this implication provides insights to the censorship circumvention community beyond the viability of specific techniques presented in this work.
Keywords: censorship; censorship circumvention; http; http request smuggling

We Really Need to Talk About Session Tickets: A Large-Scale Analysis of Cryptographic Dangers with TLS Session Tickets - Hebrok, Sven Niclas; Nachtigall, Simon; Maehren, Marcel; Erinola, Nurullah; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (32nd USENIX Security Symposium)

Re-Envisioning Industrial Control Systems Security by Considering Human Factors as a Core Element of Defense-in-Depth - Pottebaum, Jens; Rossel, Jost; Somorovsky, Juraj; Acar, Yasemin; Fahr, René; Arias Cabarcos, Patricia; Bodden, Eric; Gräßler, Iris (2023 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW))
The security of Industrial Control Systems is relevant both for reliable production system operations and for high-quality throughput in terms of manufactured products. Security measures are designed, operated and maintained by different roles along product and production system lifecycles. Defense-in-Depth as a paradigm builds upon the assumption that breaches are unavoidable. The paper at hand provides an analysis of roles, corresponding Human Factors and their relevance for data theft and sabotage attacks. The resulting taxonomy is reflected by an example related to Additive Manufacturing. The results assist in both designing and redesigning Industrial Control System as part of an entire production system so that Defense-in-Depth with regard to Human Factors is built in by design.
Keywords: Defense-in-Depth; Human Factors; Production Engineering; Product Design; Systems Engineering

Security Analysis of the 3MF Data Format - Rossel, Jost; Mladenov, Vladislav; Somorovsky, Juraj (Proceedings of the 26th International Symposium on Research in Attacks, Intrusions and Defenses)
3D printing is a well-established technology with rapidly increasing usage scenarios both in the industry and consumer context. The growing popularity of 3D printing has also attracted security researchers, who have analyzed possibilities for weakening 3D models or stealing intellectual property from 3D models. We extend these important aspects and provide the first comprehensive security analysis of 3D printing data formats. We performed our systematic study on the example of the 3D Manufacturing Format (3MF), which offers a large variety of features that could lead to critical attacks. Based on 3MF’s features, we systematized three attack goals: Data Exfiltration (dex), Denial of Service, and UI Spoofing (uis). We achieve these goals by exploiting the complexity of 3MF, which is based on the Open Packaging Conventions (OPC) format and uses XML to define 3D models. In total, our analysis led to 352 tests. To create and run these tests automatically, we implemented an open-source tool named 3MF Analyzer (tool), which helped us evaluate 20 applications.
Keywords: Data Format Security; 3D Manufacturing Format; 3D Printing; Additive Manufacturing

Poster: Circumventing the GFW with TLS Record Fragmentation - Niere, Niklas; Hebrok, Sven Niclas; Somorovsky, Juraj; Merget, Robert (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)
State actors around the world censor the HTTPS protocol to block access to certain websites. While many circumvention strategies utilize the TCP layer only little emphasis has been placed on the analysis of TLS-a complex protocol and integral building block of HTTPS. In contrast to the TCP layer, circumvention methods on the TLS layer do not require root privileges since TLS operates on the application layer. With this proposal, we want to motivate a deeper analysis of TLS in regard to censorship circumvention techniques. To prove the existence of such techniques, we present TLS record fragmentation as a novel circumvention technique and circumvent the Great Firewall of China (GFW) using this technique. We hope that our research fosters collaboration between censorship and TLS researchers.

"I don' know why I check this..." - Investigating Expert Users' Strategies to Detect Email Signature Spoofing Attacks - Mayer, Peter; Poddebniak, Damian; Fischer, Konstantin; Brinkmann, Marcus; Somorovsky, Juraj; Sasse, Angela; Schinzel, Sebastian; Volkamer, Melanie (Eighteenth Symposium on Usable Privacy and Security (SOUPS 2022))

TLS-Anvil: Adapting Combinatorial Testing for TLS Libraries - Maehren, Marcel; Nieting, Philipp; Hebrok, Sven Niclas; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (31st USENIX Security Symposium (USENIX Security 22))

On the Security of Parsing Security-Relevant HTTP Headers in Modern Browsers - Siewert, Hendrik; Kretschmer, Martin; Niemietz, Marcus; Somorovsky, Juraj (2022 IEEE Security and Privacy Workshops (SPW))
Web browsers are among the most important but also complex software solutions to access the web. It is therefore not surprising that web browsers are an attractive target for attackers. Especially in the last decade, security researchers and browser vendors have developed sandboxing mechanisms like security-relevant HTTP headers to tackle the problem of getting a more secure browser. Although the security community is aware of the importance of security-relevant HTTP headers, legacy applications and individual requests from different parties have led to possible insecure configurations of these headers. Even if specific security headers are configured correctly, conflicts in their functionalities may lead to unforeseen browser behaviors and vulnerabilities. Recently, the first work which analyzed duplicated headers and conflicts in headers was published by Calzavara et al. at USENIX Security [1]. The authors focused on inconsistent protections by using both, the HTTP header X-Frame-Options and the framing protection of the Content-Security-Policy. We extend their work by analyzing browser behaviors when parsing duplicated headers, conflicting directives, and values that do not conform to the defined ABNF metalanguage specification. We created an open-source testbed running over 19,800 test cases, at which nearly 300 test cases are executed in the set of 66 different browsers. Our work shows that browsers conform to the specification and behave securely. However, all tested browsers behave differently when it comes, for example, to parsing the Strict-Transport-Security header. Moreover, Chrome, Safari, and Firefox behave differently if the header contains a character, which is not allowed by the defined ABNF. This results in the protection mechanism being fully enforced, partially enforced, or not enforced and thus completely bypassable.

ALPACA: Application Layer Protocol Confusion - Analyzing and Mitigating Cracks in TLS Authentication - Brinkmann, Marcus; Dresen, Christian; Merget, Robert; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schwenk, Jörg; Schinzel, Sebastian (30th USENIX Security Symposium (USENIX Security 21))

Raccoon Attack: Finding and Exploiting Most-Significant-Bit-Oracles in TLS-DH(E) - Merget, Robert; Brinkmann, Marcus; Aviram, Nimrod; Somorovsky, Juraj; Mittmann, Johannes; Schwenk, Jörg (30th USENIX Security Symposium (USENIX Security 21))

Automated Detection of Side Channels in Cryptographic Protocols: DROWN the ROBOTs! - Drees, Jan Peter; Gupta, Pritha; Hüllermeier, Eyke; Jager, Tibor; Konze, Alexander; Priesterjahn, Claudia; Ramaswamy, Arunselvan; Somorovsky, Juraj (14th ACM Workshop on Artificial Intelligence and Security)